Assessing New Types of Distance Learning Programs: A Case Study Based on Educational Expectations - Luévano de la Cruz, Karla Olimpia (2020)
The Program for Strengthening Educational Quality (PFCE) is an initiative of the Government of Mexico to support State Universities through the extension of additional resources. The main objective of this PFCE-supported study, was to assess a new distance learning program option to help reduce migration of youngsters to the capital city, other states or abroad. It was determined that the main factors that impact educational perspectives of high school students in three cities in the state of Durango, was based on three sources: The individual opinion of the student regarding their personal, academic, family and social needs, their parents´ points of view about their children´s academic future, varying economic and social contexts, and, lastly, current needs and perspectives of the region´s employers based on their own experience. This case study is based on a cross-cutting methodology through three surveys. The collected data was processed through SPSS, focus groups and interviews. The results reveal that students were particularly interested in pursuing Health and Social Sciences, Technology, Natural and Exact Sciences, Geology, Agriculture, Education and Business in a distance setting. Recommendations were made that the three cities that participated in the study make efforts to expand and enhance Internet connectivity in order to favor distance learning options, which also include Continuing Education Programs for adults, particularly Business Training Programs. This study is relevant since it aims to provide contextualized educational programs for specific fields of study and, therefore, help contribute to social and economic development of the region in the medium and long-term.